Conspiracism on social media: An agenda melding of group-mediated deceptions. (1st June 2020) - Bantimaroudis, Philemon; Sideri, Maria; Ballas, Dimitris; Panagiotidis, Theodore; Ziogas, Thanasis
This study examines students' social media interactions in relation to their subcultural explorations of a conspiratorial nature. A sample of 476 students from four European universities participated in a survey about conspiracy theories in social media group discussions. In the survey, we examined various social and media factors in relation to students' beliefs in conspiracy theories. The results of this exploratory study reveal that students treat social media as news sources; furthermore, they trust social media more than traditional mass media. The study reveals demographic, personal and technological factors that encourage a mediated conspiratorial discourse.